2019
DOI: 10.1089/tmj.2018.0039
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Rural End-Users' Acceptance of e-Health in Developing Countries: A Study on Portable Health Clinic in Bangladesh

Abstract: The study provides guidelines for the successful adoption of e-health among rural communities in developing countries. This also creates an opportunity for e-health technology developers and service providers to have a better understanding of their end users.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 41 publications
(57 reference statements)
4
56
2
Order By: Relevance
“…A study from rural Bangladesh found that ''social reference,'' that is, when people are influenced by important peers, had the strongest impact on attitudes toward e-health. 39 In our study, there were no differences between referral and referring hospitals in how much social influence affected attitudes. However, the correlation was stronger among women compared with men, and for nurses compared with physicians, but did not reach significance ( p 0.07 and p 0.07, respectively).…”
Section: Additional Factors Influencing Acceptabilitycontrasting
confidence: 50%
See 1 more Smart Citation
“…A study from rural Bangladesh found that ''social reference,'' that is, when people are influenced by important peers, had the strongest impact on attitudes toward e-health. 39 In our study, there were no differences between referral and referring hospitals in how much social influence affected attitudes. However, the correlation was stronger among women compared with men, and for nurses compared with physicians, but did not reach significance ( p 0.07 and p 0.07, respectively).…”
Section: Additional Factors Influencing Acceptabilitycontrasting
confidence: 50%
“…We found correlations between 8 of the 11 proposed hypotheses: CO-PU, PEOU-PU, IM-ATT, SI-ATT, ANX-ATT, PEOU-ATT, PU-ATT, and ATT-BI. When we tested if there were any differences between gender, type of facility, between doctors and nurses, and their experience in burn care, we found differences between men and women in PU-ATT, and between referral and referring hospitals in the constructs CO-PU and (38) The senior management of this facility will be helpful in the use of such an app (39) In general, the facility management will be supportive of the use of an app of this kind (40) In general, the district health services management will be supportive of the use of such an app IM-ATT. Because of the small sample size, many constructs did not converge in the analysis.…”
Section: (16)mentioning
confidence: 99%
“…Telemedicine is a technology-based healthcare system that can contribute to better health management by integrating ICT, clinics and the internet to provide teleconsultation between clinicians and patients (Kiberu, Mars, & Scott, 2017). Rural communities in developing countries are deprived of quality health services because of poor ICT infrastructure (Hossain, Yokota, Sultana, & Ahmed, 2018). However, in Bangladesh the ICT sector has grown considerably in recent years, demonstrating an outstanding dominating position.…”
Section: Technological Barriersmentioning
confidence: 99%
“…Kiberu et al (2017) found that equipment costs, and insufficient human resources allocations are considered to be potential resources barriers to telemedicine adoption. The literature further reports that change resistance among patients and health staff, human resources, uncertainty of ownership, ICT skills, policymaking, leadership and coordination, monitoring and evaluation, cultural and language barriers (Fanta, Pretorius, & Erasmus, 2015), service delivery issues (Hossain et al, 2018), hardware access (Boonstra & Broekhuis, 2010), financial resources allocation (E. Miller, 2010), resources allocation (Boonstra & Broekhuis, 2010), legal and ethical factors (Anderson, 2007), and appropriate equipment are dominant resource barriers to telemedicine adoption. Weinstein et al (2014) mentioned that the cost, allocation of funding for equipment and the recruitment of physicians are considered the dominant barriers to telemedicine adoption.…”
Section: Resource Allocation Barriersmentioning
confidence: 99%
“…New methods and tools in the healthcare sector are growing gradually through the continuing innovation in medicine and technologies [1]. Along with the scarcity of medical infrastructure (e.g., clinic and doctors) and the speedy advancement in Information and Communication Technology (ICT), remote healthcare systems, such as eHealth, mHealth, telemedicine, and telemonitoring, are receiving paramount consideration worldwide [2]. More than half of the world's population does not receive all of the essential services that they need.…”
Section: Introductionmentioning
confidence: 99%